Causas proximais da coexistência de duas espécies simpátricas de aranhas errantes do gênero Ctenus (Ctenidae): percepção de habitats, presas e predadores - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
The study of the interaction between pairs of species is the basis for understanding the coexistence in biological communities. The ability to select habitats may be important in the coexistence of competing species and in the interactions between predators and prey. This selection is often associated with the capacity of perception of chemical cues of prey and structural components of the habitat. The perception and response to chemical cues have been demonstrated for wandering spiders, but only for the family Lycosidae in temperate regions. The soil is among the structural factors that affect habitat selections in spiders, but this has been demonstrated only for burrowing spiders. In tropical forests, high biological diversity and the rapid degradation may hinder the recognition of cues from multiple species of predators and prey. Habitat selection based on different soil types may be important in this ecosystem where drastic soil alternations are common between nearby sites, especially if the soil type is related to some important resource. We assessed the response of two species of wandering spiders in a forest in central Amazonia, Ctenus amphora Melo-Leitão 1930 and Ctenus crulsi Melo-Leitão 1930 (Araneae, Ctenidae) (1) to chemical cues from potential prey, crickets Gryllus assimilis (Fabricius, 1775) (Orthoptera, Gryllidae) and termites Syntermes Holmgren, 1910 (Isoptera, Termitidae), (2) to chemical cues from predators, spiders Phoneutria Perty, 1833 (Araneae, Ctenidae) and army ants Labidus praedator (Fr. Smith, 1858 ) (Formicidae, Ecitonini), (3) and two soil types, sandy and clay soils on which the distribution and abundance of these species diverge. For the first two evaluations we compared the proportion of time on filter paper with and without the chemical cues, to the third evaluation we compared the proportion of time on the two types of soil. These observations were performed over 09 hours with 54 observations per spider at intervals of 10 minutes. A total of 65 spiders were observed in the experiment with prey (termites cues, crickets cues and control), 36 in the experiment with predators Phoneutria (Phoneutria cues and control), 15 in the experiment with army ants (army ants cues and control) and 67 spiders in the soil experiment. The two species spent significantly longer time on the filter paper with chemical cues from the 9 prey, which indicates that the perception of cues can be important for the foraging of the two species. Although C. crulsi consumes far more Syntermes termites in natural conditions, the two species did not differ in the proportion of time on the cues from termites in comparison to the time on cues from crickets, sugesting that they do not differ in the ability to detect the chemical from these prey. No antipredator response was detected for the two species of Ctenus. Therefore, there is no evidence that the coexistence of these species is facilitated by differences in the perception of chemical cues. Only C. crulsi presented preference to a type of soil, the clay soil, which coincides with the type of soil where it is found in abundance in nature. This response of C. crulsi can influence the distribution of C. amphora, due to interactions of these species. Therefore, the perception of soil type is probably an important proximal factor in determining the distribution patterns and dynamics of coexistence of these species.
Keywords: Araneae; Comportamento antipredatório; Comunicação química; Interações entre espécies; Labidus praedator; Percepção de presa; Preferência por tipo de solo; Syntermes; Antipredator behavior; Chemical communication; Interactions between species; Labidus praedator; Prey perception; Preference for a type of soil; Phoneutria; Habitat selection; CIÊNCIAS BIOLÓGICAS